In Transit: Placelessness and the Absurd in the Writings of Anna Seghers. Issue 1 (2nd January 2020) - Kearns, Gerry
Abstract : The structure of feeling that has been called the absurd suggests a placeless and irrational world. Yet such a structure of feeling is sometimes produced in response to quite a specific context. This essay considers the way absurdity arises and is treated within Anna Seghers's Transit, a novel about the plight of refugees from Nazi Germany trying to leave unoccupied France after the signing of the Armistice between France and Germany in June 1940. The essay explores the treatment of space and time in the novel and suggests that there is a significant distinction between absurdity as resignation and absurdity as dissent. The essay also claims that absurdity is explicitly countered in the novel in the pursuit of a politics of responsibility and a resistance in solidarity.